2019
DOI: 10.3390/f10040314
|View full text |Cite
|
Sign up to set email alerts
|

Short Rotation Eucalypts: Opportunities for Biochar

Abstract: Eucalypts can be very productive when intensively grown as short rotation woody crops (SRWC) for bioproducts. In Florida, USA, a fertilized, herbicided, and irrigated cultivar planted at 2471 trees/ha could produce over 58 green mt/ha/year in 3.7 years, and at 2071 trees/ha, its net present value (NPV) exceeded $750/ha at a 6% discount rate and stumpage price of $11.02/green mt. The same cultivar grown less intensively at three planting densities had the highest stand basal area at the highest density through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…Therefore, wider spacings, such as S3 and S4, will present a greater basal area than those with the lowest density, such as S1 and S4. This result agrees with the eucalyptus species growing in SRC (Rockwood et al 2019). On the other hand, it is observed that in C. alliodora (Fig.…”
Section: Mortality and Growthsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, wider spacings, such as S3 and S4, will present a greater basal area than those with the lowest density, such as S1 and S4. This result agrees with the eucalyptus species growing in SRC (Rockwood et al 2019). On the other hand, it is observed that in C. alliodora (Fig.…”
Section: Mortality and Growthsupporting
confidence: 90%
“…There are different species that can be used in SRC systems . In temperate climates, there are Populus, Salix, Pinus, Robinia, and Eucalyptus in the EU region (Amichev et al 2014;Djomo et al 2015;Pleguezuelo et al 2015), and in Latin America, a great diversity of species in the SRC, between 35 and 40 species (Moya et al 2019), probably due to the great adaptability of the species to different soil conditions (Rockwood et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the tree growth response to biochar addition can be highly variable and specific to particular environments or tree species (Heiskanen et al, 2013;Thomas and Gale, 2015;Lin et al, 2017;Li et al, 2018;Rockwood et al, 2019;Sarauer et al, 2019). Growth responses are especially pronounced at early growth stages (Robertson et al, 2012;Pluchon et al, 2014;Thomas and Gale, 2015;Lefebvre et al, 2019), and the growth responses appear to be higher in boreal and tropical than in temperate forests (Thomas and Gale, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Improved growth because of the added fertilizer was expected at this site. Foresters on Guam are currently experimenting with mixing biochar into planting holes to improve tree growth [36,37].…”
Section: Seedling Growthmentioning
confidence: 99%